A View of Humanitarian Law on Treason in Court Decisions in Indonesia: A Legal Analysis - Permanasari, Arlina; Wibowo, Aji; Angelica H., Nadia; Salsabilah, Nahdia (UNISSULA, 2025)
The 1949 Geneva Conventions set out clear obligations for participating states to uphold the humanitarian norms contained therein. In Indonesia, the two regions of Aceh and Papua have experienced violent conflict with significant escalation, raising the question of whether these situations can be legally classified as non-international armed conflicts under international humanitarian law. The purpose of this study is to examine this issue by focusing on how treason cases have been tried in Indonesian courts, as judicial reasoning provides an important perspective for assessing the threshold of violence. This study uses normative legal methods, reviewing relevant statutory provisions, legal principles, and court decisions. The research findings indicate that, from a humanitarian law perspective, the acts of violence in Aceh and Papua have not reached the legal threshold required to be categorized as non-international armed conflicts. Instead, the handling of treason crimes still relies on national legal instruments, particularly Article 7 paragraph (2) of the Indonesian National Armed Forces Law, which frames such acts as military operations other than war. In conclusion, although these conflicts exhibit significant social and political tensions, they remain outside the scope of humanitarian law, highlighting the reliance on criminal law and military law in addressing treason.